2001
DOI: 10.1126/science.292.5521.1546
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of DNase II for Definitive Erythropoiesis in the Mouse Fetal Liver

Abstract: Mature erythrocytes in mammals have no nuclei, although they differentiate from nucleated precursor cells. The mechanism by which enucleation occurs is not well understood. Here we show that deoxyribonuclease II (DNase II) is indispensable for definitive erythropoiesis in mouse fetal liver. No live DNase II-null mice were born, owing to severe anemia. When mutant fetal liver cells were transferred into lethally irradiated wild-type mice, mature red blood cells were generated from the mutant cells, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
306
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(319 citation statements)
references
References 25 publications
11
306
1
1
Order By: Relevance
“…Interestingly, inhibition of the ability of plasmatocytes to engulf bacteria by the prior application of polystyrene beads into the body cavity results in a significant loss of viability in flies carrying a mutation in the humoral response [40]. Interestingly the negative effect mediated by bead accumulation in plasmatocytes resembled the deleterious effect of accumulation of apoptotic nuclei in macrophages of dnase II -/-mice [10]. Due to this resemblance, we predicted that the loss of DNase II activity would result in the accumulation of DNA within phagocytic cells with a concomitant loss of immune function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, inhibition of the ability of plasmatocytes to engulf bacteria by the prior application of polystyrene beads into the body cavity results in a significant loss of viability in flies carrying a mutation in the humoral response [40]. Interestingly the negative effect mediated by bead accumulation in plasmatocytes resembled the deleterious effect of accumulation of apoptotic nuclei in macrophages of dnase II -/-mice [10]. Due to this resemblance, we predicted that the loss of DNase II activity would result in the accumulation of DNA within phagocytic cells with a concomitant loss of immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Although an increase in antimicrobial peptide production would be expected to partially compensate for the loss of hemocyte function, this was clearly not the case. This perplexing result is reminiscent of the embryonic lethality observed in dnase II-knockout mice which is caused by an unexpected overexpression of INF-β by macrophages [10][11][12]. Apart from antimicrobial peptide induction, it has been demonstrated that dDNase II itself is significantly induced by bacterial and fungal infection [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNase II is responsible for digesting the DNA of apoptotic cells after macrophages engulf them, and many macrophages carrying engulfed DNA are present in DNase IIdeficient embryos. [20][21][22] Here, we used DNase II-deficient mice to detect the programmed cell death that occurs during mouse development, and found that Apaf-1 seems to be dispensable for this process. In the thymus of Apaf-1 À/À embryos at E14.5, caspases were activated in an Apaf-1-independent manner.…”
mentioning
confidence: 99%
“…It has been shown by Kawane and colleagues that mice lacking the lysosomal endonuclease DNAse II (Dnase II -/-mice) are embryonically lethal, due to the impaired ability to degrade self-DNA by macrophages (Kawane et al, 2001). Genomic deletion of type I IFN Receptor (IFNAR) rescued Dnase II -/-mice from embryonic lethality (Yoshida et al, 2005), but the mice lacking both IFNAR and DNAse II (Dnase II -/-Ifnar -/-mice) would develop polyarthritis (Kawane et al, 2001). Interestingly, Baum and colleagues demonstrated a peculiar role for the AIM2 inflammasome in arthritis pathogenesis.…”
Section: Aim2 In Autoimmunity and Skin Diseasesmentioning
confidence: 99%